Glycosylated zein as a novel nanodelivery vehicle for lutein. (15th May 2022) - Chang, Ying; Jiao, Yan; Li, Da-Jing; Liu, Xiao-Lan; Han, He
Highlights: The zein was modified with glucosamine by transglutaminase-induced glycosylation. A novel lutein delivery vehicle was successfully fabricated by glycosylated zein. Glycosylation improved entrapment efficiency of lutein in zein nanoparticles. The glycosylated zein nanoparticles improved the solubility of lutein about 10 times. Glycosylated zein nanoparticles showed higher release of lutein and better antioxidant activity. Abstract: Glucosamine-glycosylated zein (GLZ) generated by transglutaminase was developed as a novel delivery vehicle to prepare lutein-loaded glycosylated zein nanoparticles (GLZ-LUT). GLZ-LUT exhibited a polydispersed spherical microstructure, lutein was embedded into GLZ to form nanocomplexes via self-assembly, they had a lower zeta potential and an average particle size of less than 200 nm. Compared to lutein-loaded zein nanoparticles (Zein-LUT), the lutein entrapment efficiency of GLZ-LUT was increased from 81.55% to 89.60%. Infrared spectroscopy (FTIR) analysis results confirmed that zein was successfully modified and that lutein was encapsulated by hydrophobic zein and GLZ. Moreover, GLZ showed significantly higher solubilization of lutein than Zein-LUT and significantly improved the in vitro release of lutein in the simulated gastrointestinal tract. The in vitro antioxidant activity of lutein was also enhanced by the encapsulation of zein and glycosylated zein. These findings indicated that GLZ represent a potentially efficient and promising nanodelivery carrier for lutein compounds.